Social Media for Health Campaign and Solidarity Among Chinese Fandom Publics During the COVID-19 Pandemic - Jiang, Qiaolei; Liu, Shiyu; Hu, Yue; Xu, Jing (Frontiers in Psychology, 2022)
Background: As a highly contagious disease, the COVID-19 pandemic has become a serious health threat and psychological burden for the global communities. From the conceptual perspective of affordances, this research examined the role of social media for health campaign and psychological support during the global crisis. Methods: Data from both social media and a nationwide survey were collected and analyzed. Face mask-related posts on Sina Weibo from January 1, 2020, to June 30, 2020, were retrieved and studied. Face mask wearing as a well-established preventive measure was identified and examined from hashtag topics. A nationwide survey with a randomized experiment embedded was conducted to further investigate the mobilizing dynamics. Results: During the escalation phase in the first half of 2020, the hashtag topic “#national mask campaign#,” initiated by a celebrity, topped the ranking of mask-related topics on Weibo. The findings indicated that prevention activities, solidarity expression, and names of celebrity idols were frequently discussed. With celebrity idols as opinion leaders, millions of fandom publics actively participated in this hashtag health campaign. Results of the nationwide survey show the popularity of fan identity, and the experiment results demonstrate the strong mobilizing power of celebrity idol and fandom community in civic engagement and participation among young Chinese. Conclusions: The research demonstrates how the affordances of social media, such as liking, commenting, reposting, and hashtagging can be influential in promoting health behaviors and expressing solidarity. Implications for public health professionals and policymakers to raise awareness and understanding about health campaigns via social media are discussed.